Attracting, equipping and retaining young medical doctors in HIV vaccine science in South Africa - Danna Flood; Melissa Wallace; Kimberly Bloch; James Kublin; Linda-Gail Bekker (AOSIS, 2015)
Background: HIV remains a significant health problem in South Africa (SA). The development of a preventive vaccine offers promise as a means of addressing the epidemic, yet development of the human resource capacity to facilitate such research in SA is not being sustained. The HIV Vaccine Trials Network (HVTN) has responded by establishing South African/HVTN AIDS Early Stage Investigator Programme (SHAPe), a programme to identify, train and retain clinician scientists in HIV vaccine research in SA. Objectives: The present study sought to identify factors influencing the attraction and retention of South African medical doctors in HIV vaccine research; to understand the support needed to ensure their success; and to inform further development of clinician research programmes, including SHAPe. Methods: Individual interviews and focus groups were held and audio-recorded with 18 senior and junior research investigators, and medical doctors not involved in research. Recordings were transcribed, and data were coded and analysed. Results: Findings highlighted the need for: (1) medical training programmes to include a greater focus on fostering interest and developing research skills, (2) a more clearly defined career pathway for individuals interested in clinical research, (3) an increase in programmes that coordinate and fund research, training and mentorship opportunities and (4) access to academic resources such as courses and libraries. Unstable funding sources and inadequate local funding support were identified as barriers to promoting HIV research careers. Conclusion: Expanding programmes that provide young investigators with funded research opportunities, mentoring, targeted training and professional development may help to build and sustain SA's next generation of HIV vaccine and prevention scientists.